Quantitative proteomics profiling of the poly(ADP-ribose)-related response to genotoxic stress - Gagné, Jean-Philippe (Oxford University Press, 2012)
Upon DNA damage induction, DNA-dependent poly(ADP-ribose) polymerases (PARPs) synthesize an anionic poly(ADP-ribose) (pADPr) scaffold to which several proteins bind with the subsequent formation of pADPr-associated multiprotein complexes. We have used a combination of affinity-purification methods and proteomics approaches to isolate these complexes and assess protein dynamics with respect to pADPr metabolism. As a first approach, we developed a substrate trapping strategy by which we demonstrate that a catalytically inactive Poly(ADP-ribose) glycohydrolase (PARG) mutant can act as a physiologically selective bait for the isolation of specific pADPr-binding proteins through its macrodomain-like domain. In addition to antibody-mediated affinity-purification methods, we used a pADPr macrodomain affinity resin to recover pADPr-binding proteins and their complexes. Second, we designed a time course experiment to explore the changes in the composition of pADPr-containing multiprotein complexes in response to alkylating DNA damage-mediated PARP activation. Spectral count clustering based on GeLC-MS/MS analysis was complemented with further analyses using high precision quantitative proteomics through isobaric tag for relative and absolute quantitation (iTRAQ)- and Stable isotope labeling by amino acids in cell culture (SILAC)-based proteomics. Here, we present a valuable resource in the interpretation of systems biology of the DNA damage response network in the context of poly(ADP-ribosyl)ation and provide a basis for subsequent investigations of pADPr-binding protein candidates.